PENGARUH PENAMBAHAN BERBAGAI JENIS SUMBER KARBOHIDRAT PADA SILASE LIMBAH SAYURAN TERHADAP KADAR LEMAK KASAR, SERAT KASAR, PROTEIN KASAR DAN BAHAN EKSTRAK TANPA NITROGEN - Fakhri Aji Amrullah; Liman ,; Erwanto . (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
Vegetable waste in the traditional market can be used as feed.  Nevertheless, the shortcomings from vegetable waste is have a high level of water content.  Vegetables waste can be processed to be silage with addition accelerators that is rice bran, cassava flour, molasses. The purpose of this research was to compare the effect of additioning some source of carbohydrate in the fermentation of the vegetable waste silage.  This research use Completely Randomized Design (CRD) with four treatments by adding source of carbohydrate as accelerator ( rice bran, cassava flour, molasses and silage without the addition of accelerators) and three repetition. Data was analyzed by Analysis of Varians and continued with Least Significant Difference Test (LSD) 0,01 or 0,05. The result of this research showed that vegetable waste silage by adding different carbohydrate sources has  highly significant (P<0,01) to the crude protein, crude fat content, and non nitrogen free extract of vegetable waste silage while the crude fiber content has not significant effect (P>0,05). The best treatment for crude protein and crude fat contents of vegetable waste silage by addition of  rice bran and cassava flour for nitrogen free extract. Keywords :silage, rice bran, cassava flour, molasses, waste silage, nutrition content.